Student‐Created Book Basket Labels: An Innovative, Culturally Sustaining Literacy Practice. (8th November 2018) - Nash, Kindel; Panther, Leah; Elson, Kerry
Abstract: A century of research has shown that culturally relevant, responsive, and sustaining literacy teaching is essential to teaching all students well and is especially crucial for students of color, who most often attend urban schools. The authors share one innovative and culturally sustaining literacy practice that critically centers kindergarten and first‐grade students' agency and language knowledge in writing and drawing labels for their classroom book baskets. When students create labels for their classroom books, they not only take ownership of their classroom library but are also positioned as real readers and real writers who are active and innovative communicators, writers, and readers of everyday texts that represent their diverse lives and experiences.